Pursuit on the plane by objects moving away from the trajectory of defending object, with simulation of detection area - A. А. Dubanov; T. V. Ausheev (Омский научный вестник)
This article describes the model of pursuit of a single target by the method of chasing a group of objects. All objects participating in the pursuit model move with a constant modulo speed. The pursuing object moves along a certain trajectory and releases objects at specified intervals, the task of which is to overtake the target by the chase method. Released objects have restrictions on the curvature of the motion path. A single target, in turn, is tasked with overtaking the pursuer by the method of parallel approach. For each pursuing object, a detection area is formed. The detection area is formed by two beams. The object's velocity vector is the bisector of the angle formed by such rays. If the target enters the detection area, then the object begins the pursuit by the chase method. If the target leaves the detection area, then the object makes a uniform and rectilinear movement. The task is to implement a dynamic model of multiple group pursuit, where each object has its own tasks, which implements the chase method. The model is developed using computer mathematics systems. Based on the results of the research, animated images are created. As an example, where the model developed in the article could be in demand, the following can be given. There is considered the motion of a low-maneuverable object that is overtaking a faster target. As a means of protection, instead of releasing passive heat traps, it is proposed to drop a multitude of autonomously controlled weapons of destruction. From the analysis of the media, descriptions of such means of protection for aircraft have not been found. Modeling is carried out on a plane, there are no obstacles for modeling in space. The results of the research can be in demand in the design of unmanned aerial vehicles with elements of autonomous control and artificial intelligence.